SISTEM INFORMASI AKADEMIK PADA SEKOLAH MENENGAH ATAS WIDYA NUSANTARA BEKASI - Wina Widiati (Swabumi, 2016)
Cademic Information Systems at SMA Widya Nusantara is relatively complex system because thesystem involves many objects such as; students, teachers, schedules and scores. Each object has a relation to one another. If the academic system of data processing is still done manually, it will cause problems for system users (teachers, students and the Students Academic section). Writer build adynamic web application that can be used to disseminate the right information, quickly and accurately, develop and update student data processing, high school teacher at Widya Nusantara. Research conducted by using the method of observation, interviews, and literature. The support equipmentused in this research histocreate a model of Entity Relationship Diagrams and the Unified Modeling Language. Based on the problems of the Academic Information System in Widya Nusantara High School, the writer intends to create aweb-based academic information systems in order to provide convenience to the teacher in informing reports of student activity. The aim istomake the processof data reporting students cores and attendance activity can be informed quickly.